Sequence variants contributing to dysregulated inflammatory responses across keratoconic cone surface in adolescent patients with keratoconus - Jaskiewicz, Katarzyna; Maleszka-Kurpiel, Magdalena; Kabza, Michał; Karolak, Justyna A.; Gajecka, Marzena (Frontiers in Immunology, 2023)
Background Keratoconus (KTCN) is the most common corneal ectasia resulting in a conical shape of the cornea. Here, genomic variation in the corneal epithelium (CE) across the keratoconic cone surface in patients with KTCN and its relevance in the functioning of the immune system were assessed. Methods Samples from four unrelated adolescent patients with KTCN and two control individuals were obtained during the CXL and PRK procedures, respectively. Three topographic regions, central, middle, and peripheral, were separated towards the whole-genome sequencing (WGS) study embracing a total of 18 experimental samples. The coding and non-coding sequence variation, including structural variation, was assessed and then evaluated together with the previously reported transcriptomic outcomes for the same CE samples and full-thickness corneas. Results First, pathway enrichment analysis of genes with identified coding variants pointed to “Antigen presentation” and “Interferon alpha/beta signaling” as the most overrepresented pathways, indicating the involvement of inflammatory responses in KTCN. Both coding and non-coding sequence variants were found in genes (or in their close proximity) linked to the previously revealed KTCN-specific cellular components, namely, “Actin cytoskeleton”, “Extracellular matrix”, “Collagen-containing extracellular matrix”, “Focal adhesion”, “Hippo signaling pathway”, and “Wnt signaling” pathways. No genomic heterogeneity across the corneal surface was found comparing the assessed topographic regions. Thirty-five chromosomal regions enriched in both coding and non-coding KTCN-specific sequence variants were revealed, with a most representative 5q locus previously recognized as involved in KTCN. Conclusion The identified genomic features indicate the involvement of innate and adaptive immune system responses in KTCN pathogenesis.